Effect of Dhatryadi Ghrithm in “Diminishing Ovarian Reserve” (International Journal of Ayurveda and Pharma Research, 2023)
Background: Diminishing ovarian reserve (DOR) describes women of reproductive age with regular cycles, mostly ovulatory, whose response to ovarian stimulation is reduced compared to women of comparable age. The most appropriate correlation of DOR can be done with Dhatukshaya Vandya. Dhatraydi Ghrithm mentioned in Sahasra Yogam is said to have implicit effect in enhancing reproductive potential.  Objectives: To evaluate the effect of Dhatryadi Ghrithm in “Diminishing ovarian reserve”.Materials and methods: It was a pre and post interventional study done during the time period July 2017 to December 2018 with a sample size of 20. Females between the age group of 20-35 years, diagnosed with DOR attending Outpatient Department of Govt Ayurveda College Hospital for Women and Children, Poojappura, Thiruvananathapuram were selected. Serum Anti Mullerian Hormone (AMH), Serum Estradiol, Antral Follicular Count (AFC) and LH/FSH ratio, Ovarian volume was assessed on the 2nd day of the cycle after completing 90 days of Ghritha administration. Paired t test was used to analysis the data statistically.  Results: 55 % of total study population were in the low fertility group and 45% confined to the very low fertility group.7 out of 20 patients obtained satisfactory level of fertility after 3 months of treatment. There was a considerable increase in mean value of AMH before and after treatment (2.62 to 9.01), p-value 0.001. AFC was also significantly increased after three months of treatment, p-value